2012
DOI: 10.1007/s00422-012-0497-3
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-specific adaptation, habituation and change detection in the gaze control system

Abstract: This prospect article addresses the neurobiology of detecting and responding to changes or unexpected events. Change detection is an ongoing computational task performed by the brain as part of the broader process of saliency mapping and selection of the next target for attention. In the optic tectum (OT) of the barn owl, the probability of the stimulus has a dramatic influence on the neural response to that stimulus; rare or deviant stimuli induce stronger responses compared to common stimuli. This phenomenon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 106 publications
(138 reference statements)
1
45
0
Order By: Relevance
“…The entopallium receives information about salient stimuli from the OT through the tectofugal pathway (Marin et al 2007;Reches and Gutfreund 2008) and may play a role in mediating orienting responses (Gutfreund 2012). We therefore examined the trial-by-trial correlations between the PDR and activity (evoked and ongoing) recorded in the entopallium.…”
Section: Trial-by-trial Correlationsmentioning
confidence: 99%
“…The entopallium receives information about salient stimuli from the OT through the tectofugal pathway (Marin et al 2007;Reches and Gutfreund 2008) and may play a role in mediating orienting responses (Gutfreund 2012). We therefore examined the trial-by-trial correlations between the PDR and activity (evoked and ongoing) recorded in the entopallium.…”
Section: Trial-by-trial Correlationsmentioning
confidence: 99%
“…More generally, recent work on non-linguistic sensory adaptation (mostly in lowlevel vision and audition) has revealed that many negative aftereffects which were originally attributed to the fatigue of neuronal feature detectors are better explained by neural populations adjusting their processing to maximize the transmission of information about the current stimulus ensemble (Brenner et al, 2000;Fairhall et al, 2001;Gutfreund, 2012;Kohn, 2007;Sharpee et al, 2006;Webster et al, 2005), which parallels recent developments in the understanding of perceptual learning in low-level perceptual tasks (Bejjanki, Beck, Lu, & Pouget, 2011;Harris, Gliksberg, & Sagi, 2012). Maximizing information transmission depends on the statistics of the environment at many different levels.…”
Section: Discussionmentioning
confidence: 99%
“…First, work on non-linguistic sensory adaptation has established that adaptation goes far beyond fatigue of feedforward feature detectors (Brenner et al, 2000;Dragoi et al, 2000;Fairhall et al, 2001;Gutfreund, 2012;Kohn & Movshon, 2004;Kohn, 2007;Sharpee et al, 2006;Webster et al, 2005). In particular, there is tentative evidence that sensory adaptation serves to increase the efficiency of the representation of sensory information, based on the statistical or distributional properties of recent sensory input.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations